Agency and the GED: Personae and Artifacts in the Figured World of a Literacy Welcome Center. (March 2017) - LaDousa, Chaise; Baldrige, Ana
Abstract: The GED test has served as a mechanism for granting high school equivalency in the United States for decades, and some states have funded tutorial services because they have imagined the GED to be a means for getting a job or increasing one's wages. Based on field research conducted in literacy welcome centers in a small city in Upstate New York, we argue that teachers' and students' discursive reflections show that they attain agency in multiple ways during participation in tutorials. On the one hand, students build and hone their skills required for successful testing. On the other hand, teachers embody the caring disposition that the world inhabited by the students lacks. We argue that the GED and its practice exams are artifacts that only partly account for the agency of teachers and students, and, when reflected on by an administrator, erase crucial aspects of that agency.